MENINGKATKAN KECERDASAN EMOSIONAL ANAK MELALUI BERMAIN PERAN PADA ANAK USIA 4-5 TAHUN DI TK ISLAM BAKTI III DESA KEMANG INDAH KECAMATAN TAMBANG KABUPATEN KAMPAR - ', Adillah; ', Zulirfan; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the emotional intelligence in children aged 4-5 years through play a role in TK Islam Bakti III Desa Kemang Indah subdistrict Mine Kampar regency. This study is kind studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 4-5 years are numbered 17 children in kindergarten Islam Bakti III , The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. t research shows that playing the role may increase emotional intelligence in children aged 4-5 years. It can be seen from the increase in the average percentage of emotional intelligence in the first cycle of 61.44% which is the criterion developing according to expectations (BSH) and an increase of 34.44% in the second cycle be 82.60% which is very good at developing criteria (BSB). So, playing the role of can improve emotional intelligence of children aged 4-5 years in TK Islam Bakti III Desa Kemang Mining District of Kampar regency.